(untitled) (Research, Society and Development, 2022)
The School Health Program (PSE) is a set of health promotion and prevention actions carried out among health and education professionals. The objective of this research is to analyze the relationship between the PSE with the quality of life and integral education. This work is an integrative literature review, carried out during the months of August and December 2022, the data used were extracted from the databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Online Library (SCIELO), Biblioteca Virtual in Health (BVS) and Latin American and Caribbean Literature in Health Sciences (LILACS). The health descriptors were: School Health Promotion; Health Policy; Integrated Health Actions. As inclusion criteria: articles written in Portuguese, free of charge and published within the time frame from 2018 to 2022. Exclusion criteria were duplicate articles, abstracts, reviews and theses. After selecting the studies, according to the inclusion and exclusion criteria, only 8 studies made up the final sample. It was concluded that the PSE develops health education actions within basic education, involving various topics such as drug use, alcohol, tobacco, eating disorders, violence, sexual abuse, bullying, among others. The program offers students clinical, nutritional, oral hygiene and ophthalmological assessments. Together with the concept of comprehensive education, the PSE collaborates to build a more developed society with a better quality of life.